2023
DOI: 10.2147/dddt.s408076
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of a Subanesthetic Dose of Esketamine Combined with Propofol in Patients with Obesity Undergoing Painless Gastroscopy: A Prospective, Double-Blind, Randomized Controlled Trial

Abstract: Purpose Patients with obesity are more susceptible to hypoxemia. Anesthetic management for patients with obesity undergoing painless gastroscopy presents a severe challenge for anesthesiologists. Esketamine is a NMDA antagonist that has been proven to be beneficial for ameliorating respiratory depression owing to its sympathomimetic effect; however, there are no relevant reports on its use in patients with obesity. We designed a randomized controlled trial to evaluate whether esketamine can be the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Forty-one patients (12.4%) in the esketamine group and 55 (16.7%) in the placebo group had hypertension (SMD, 0.12). The median (IQR) procedure time was 20 (16)(17)(18)(19)(20)(21)(22)(23)(24)(25) minutes in the esketamine group and 18 (15)(16)(17)(18)(19)(20)(21)(22) minutes in the placebo group (SMD, 0.15).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty-one patients (12.4%) in the esketamine group and 55 (16.7%) in the placebo group had hypertension (SMD, 0.12). The median (IQR) procedure time was 20 (16)(17)(18)(19)(20)(21)(22)(23)(24)(25) minutes in the esketamine group and 18 (15)(16)(17)(18)(19)(20)(21)(22) minutes in the placebo group (SMD, 0.15).…”
Section: Resultsmentioning
confidence: 99%
“…Eberl et al 22 enrolled 162 patients undergoing endoscopic retrograde cholangiopancreatography and demonstrated that esketamine (0.15 mg/kg) led to reduced propofol requirements compared with alfentanil (2 μg/kg), without affecting recovery time or adverse events. Another study, 24 which involved 114 patients with obesity undergoing gastroscopy, found that the combination of propofol and esketamine (0.25 mg/kg) resulted in a shorter induction time and awakening time, lower propofol consumption, more stable hemodynamics, and a reduced incidence of adverse events compared with propofol alone. Specifically, the incidence of hypoxemia was 17.3% in the esketamine group vs 40.4% in the control group, and the incidence of hypotension was 7.7% in the esketamine group vs 23.1% in the control group.…”
Section: Discussionmentioning
confidence: 99%